PENDAFTARAN TANAH MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 DAN PROYEK OPERASIONAL AGRARIA (PRONA) DI KOTA TIDORE KEPULULAUAN - Kasim, Husain (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
The study was conducted in Tidore Islands, the territory is mostly made up of islands. The reason the author is to determine what difficulties are encountered if the registration was done in the land-pualau island, far away from the district capital. The purpose of research that the author carried out is untuuk determine the factors that become an obstacle for the landowner in registering the land and figure out the constraints faced by the authorities in charge of organizing the registration of land and containment of these constraints.The research method used by the writer, is; (1) research literature, was done by examining the books, documents and other papers, in order to collect secondary data; (2) field research, conducted by the author went to the field to interview the respondents (landowners who have and have not register their land) and the source (officials at the local Land Office and the other relevant agencies).Analysis used in managing the data collected, is the quantitative and qualitative analysis and after it had been described.Results of the study revealed that most residents do not know and understand very well about the registration of land as well as the legal consequences of registration itself, otherwise it will be the cost of land registration is still considered expensive by citizens, as well as factors bureaucracy and lack of executive power professionals.